Motif-Motif Tenun di Desa Mabolu Kecamataan Lohia Kabupaten Muna - La Ode Kadir; La Ode Dirman; La Ode Marhini (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The objectives of this study were (1) to find out what knowledge is known by the community about woven cloth motifs ini mabolu Village. Lohia District, Muna Regenci. (2) To describe the function of Woven fabric of Motifs in Mabolu Village, Lohia District, Regenci. This research uses a qualitative descriptive method. The research location chosen was in mabolu Village. Lohia District, Muna Regency. Data collection techniques were carried out by direct observation (observation), interviewsto purposive. Data were analyzed in three stages, namely; (1) data editing, (2) data review, (3) drawing conclusions. Informants in this study amounted to 5 people, data collection in this study was carried out using observation techniques, interviews and documentation which were then analyzed descriptively qualitatively. The resultsof this study are; (1) knowledge the community regarding motives there are 12 motifs along with the groups that use them, namely the bhia-bhia motif for walaka, the samasili motif for kaomu, the lante-lante motif for maradika or small people, the kambeano bhontu motif for walaka, the bhotu motif for kaomu, the kambeano sirikaea motif for kaomu, bharalu motif for walaka, kambeano kuni motif for kaomu, manggo-manggopa motif for kaomu, mosituli motif for kaomu, ledha motif for walaka, kambeano bhanggai motif for kaomu, (20 There are 3 functions of the wuna woven sarong, namely for prayer, sleeping and for sacred events.